EPC Agenda 2005-04-14 - Academic Senate:::::::::
Educational Policies Committee. Special Student Report. Agenda – Approved. Minutes of 2/4/2021 – Approved. Chair Report. Consent Item: Faculty Eligible for Emeritus Status – Gregory Roberts – Approved. President Report. Provost Report. From FSAC: RTP revisions discussion. From S&F: By-law change membership of URTP – First Reading completed. Posthumous Certificate for Luis Cid – Approved. Posthumous Degree Approved for Alondra Bandt. Motion that the Academic Senate endorse the EPC statement on administrative encroachment into curricular matters. Second - Postponed to next meeting. Vice Chair Report. Vice President for Student Affairs Report. Statewide Senators Report.